Risk in Funding Infrastructure Projects through Sukuk or Islamic Bonds - Abdullah, Abdul Aziz; Yazid, Ahmad Shukri; Abdullah, Adam; Kamarudin, Mohd Shahril (International Review of Management and Business Research, 2014)
The funding of infrastructure projects via the issuance of sukuk or Islamic bonds is emerging as a popular funding alternative to conventional bonds. However, there are certain risks when funding infrastructure projects. This paper aims to identify and profile risks associated with funding infrastructure projects from the issuance of sukuk, through a rigorous review of literature. These risks will be structured in order to formulate those risks associated from the issuance of sukuk. This paper will also assess risks that transpire from issuing of sukuk to fund infrastructure projects. By identifying the sukuk risk, it should enable stakeholders to address related funding issues.